PENGARUH RESIKO KEUANGAN, CASH HOLDING, BONUS PLAN DAN PAJAK PENGHASILAN TERHADAP PERATAAN LABA PADA PERUSAHAAN X PERIODE 2021-2022 - Vicario, Vanessa (MANABIS: Jurnal Manajemen dan Bisnis, 2023)
Xis a company engaged in the furniture sector. The purpose of this research is to determine and analyze the effect of financial risk, cash holding, bonus plans and income tax on income smoothing at Perusahaan Xfor the period 2021-2022. The population as well as the sample of this research is data on total debt, total assets, cash, current debt, monthly bonus, income tax, income and expenses at Perusahaan Xfor the period 2021-2022. The total population is 4 years x 12 months = 48. This research method uses multiple linear regression analysis. The results showed that financial risk had no effect on income smoothing at Company X for the period 2021-2022. Cash holding has no effect on income smoothing at Company X for the period 2021-2022. The bonus plan has no effect on income smoothing at Company X for the period 2021-2022. Income tax has an effect on income smoothing at Company X for the period 2021-2022. Financial risks, cash holding, bonus plans and income taxes have an effect on income smoothing at Company X for the period 2021-2022